Treating substance abuse : theory and technique - Rotgers, Frederick; Walters, Scott T. (New York : Guilford Press, 2012)
"Widely adopted, this state-of-the-art text and clinical resource captures the breadth of current knowledge about substance abuse and its treatment. For each of the major evidence-based treatment approaches, a chapter on basic assumptions and theories is followed by a chapter on clinical applications, including illustrative case material. Expert contributors cover motivational, contingency management, cognitive-behavioral, 12-step, family, and pharmacological approaches. Concluding chapters discuss effective ways to integrate different treatments in a range of clinical settings. New to This Edition*Reflects significant advances in research and clinical practice.*Restructured to follow the typical sequence of treatment.*Chapter on the biology of substance use disorders.*Chapter on an additional treatment setting: primary care.*Chapter on case management."--Provided by publisher.
Machine generated contents note: Introduction, Scott T. Walters and Frederick Rotgers 1. Theories of Motivation and Addictive Behavior, Gary S. Rose and Scott T. Walters 2. Motivational Interviewing in Practice, Erin M. Tooley and Theresa B. Moyers 3. The Behavioral Economics of Substance Abuse, James G. Murphy, James MacKillop, Rudy E. Vuchinich, and Jalie A. Tucker 4. Contingency Management in Substance Abuse Treatment, Jesse Dallery, Alan J. Budney, and Steven E. Meredith 5. Cognitive-Behavioral Theories of Substance Abuse, Frederick Rotgers 6. Behavioral Treatment Techniques for Psychoactive Substance Use Disorders, James S. Marinchak and Thomas J. Morgan 7. Theory of 12-Step-Oriented Treatment, John Wallace 8. Facilitating 12-Step Recovery from Substance Abuse, Joseph Nowinski 9. Theoretical Bases of Family Approaches to Substance Abuse Treatment, Barbara S. McCrady, Benjamin O. Ladd, and Kevin A. Hallgren 10. Family Therapy Techniques for Substance Abuse Treatment, Wendy K. K. Lam, Timothy J. O'Farrell, and Gary R. Birchler 11. Neurobiological Bases of Addiction Treatment, Phillip H. Chung, Julie D. Ross, Sidarth Wakhlu, and Bryon Adinoff 12. Integrating Psychotherapy and Pharmacotherapy in Substance Abuse Treatment, Kathleen M. Carroll and Brian D. Kiluk 13. Addressing Substance Abuse in Primary Care Settings: Screening and Brief Intervention, Kristen L. Barry and Frederic C. Blow 14. Integration of Theory, Research, and Practice: A Clinician's Perspective, Edward Rubin 15. Case Management in Substance Abuse Treatment, Allen Zweben.
Includes bibliographical references and index.
Keywords: Substance abuse -- Treatment